Analysis of the Virus Contamination and Disinfection Effect in Isolation Ward of Patients With COVID-19 - Zhang, Shiyang; Wang, Chuanpeng; Lin, Minqiang; Deng, Qinsheng; Ye, Yuzhen; Li, Zhiyong; Qiu, Lixin; Wang, Zhanxiang (Frontiers in Public Health, 2020)
The recent outbreak of COVID-19 has infected a large number of patients, increasing the importance of adequate disinfection of the hospital environment. We conducted this study to explore environmental virus contamination and the effect of terminal disinfection in the isolation ward of patients with COVID-19. A swab kit was used to sample various surfaces in the isolation and observation wards using the smear method. The samples were immediately sent to the PCR department of the laboratory for nucleic acid detection of COVID-19. We analyzed 31 high-frequency contact sites in three isolation wards of actively sick patients, of which seven were positive (22.58%, 7/31). Positive sites included the transfer window, bed rail, buffer room door handle, toilet door handle, and toilet faucet. All 55 samples taken from the wards of cured patients and the wards after terminal disinfection were negative. Virus contamination in areas frequently touched by patients in the isolation ward was high, so the awareness of correct disinfection must be increased. Use of 1,000–2,000 mg/L chlorine-containing disinfectant in the isolation ward was effective.